Pengaruh Media Benda Konkret Terhadap Hasil Belajar IPA Siswa Kelas V SDN 091538 Huta Bayu Raja - Ristika Ulyartha Silalahi; Natalina Purba; Maria Barus (PIJAR: Jurnal Pendidikan dan Pengajaran, 2024)
The aim of this research is to find out whether concrete object media influences the science learning outcomes of class V students at SDN 091538 Huta Bayu Raja or not. There are 2 hypotheses in this research, namely, (1) there is an influence of the use of concrete object media on the learning outcomes of fifth grade students at SDN 091538 Huta Bayu Raja (Ha) and (2) there is no influence of the use of concrete object media on the science learning outcomes of fifth grade students at SDN 091538 Huta Bayu Raja (H0). This research method is an experimental method with a Pre-Experimental Design type of research using the "One Group Pretest Posttest Design" design. The population of this research is all 30 class V students at SDN 091538 Huta Bayu Raja. Data collection was carried out using test and observation techniques. then the experimental class pretest score was obtained with an average value of 58.3. experimental class post-test with an average score of 83.3. So it can be concluded that there is an influence of concrete object media on the science learning outcomes of fifth grade students at SDN 091538 Huta Bayu Raja.